Phytoplankton Diversity as Bioindicator of Water Quality in Mangrove Area of Surabaya East Coast - Novirina Hendrasarie; Sucahyaning Wahyu Trihastika Kartika (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
Mangrove forests in Surabaya's estuaries and coastal areas are designated by the government as protected areas. However, in the last decade, water pollution in the estuary and coastal areas of Surabaya has increased. This is due to rivers and tributaries that lead to the estuary carrying garbage and waste, as a result the waters in the mangrove area began to be polluted. The purpose of this study was to map water pollution in the Mangrove area, using the plankton diversity index. This diversity is based on the sensitivity of plankton, so it is used as a bioindicator of water pollution. This study, conducted in the estuary and along the East Coast of Surabaya. The results showed 70% of phytoplankton abundance in Wonorejo Mangrove is influenced by the value of COD, TSS, salinity, and phosphate. The estuary and coastal Mangrove Gunung Anyar 92% is influenced by the parameter values of temperature, COD, current strength, and salinity. Bacillariophyceae and Coscinodiscophyceae were the dominant phytoplankton in the Wonorejo and Gunung Anyar mangrove areas, respectively. The dominance of these two plankton, which were able to survive, indicates that the water quality in the Wonorejo and Gunung Anyar estuaries is polluted.